Diversification in Indian agriculture towards high-value crops: The role of smallholders - Birthal, Pratap Singh; Joshi, Pramod Kumar; Roy, Devesh; Thorat, Amit (International Food Policy Research Institute, 2007)
Agricultural diversification towards high-value crops can potentially increase farm incomes, especially in a country like India where demand for high-value food products has been increasing more quickly than that for staple crops. Indian agriculture is overwhelmingly dominated by smallholders, and researchers have long debated the ability of a smallholder-dominated subsistence farm economy to diversify into riskier high-value crops. Here, we present evidence that the gradual diversification of Indian agriculture towards high-value crops exhibits a pro-smallholder bias, with smallholders playing a proportionally larger role in the cultivation of vegetables versus fruits. The observed patterns are consistent with simple comparative advantage-based production choices. The comparatively high labor endowments of the small farmers, as reflected in their greater family sizes, induce them to diversify towards vegetables. Although fruit cultivation is also labor intensive (as compared to cultivation of staples), fruits are relatively capital intensive, making them a less advantageous choice for smallholders who tend to have low capital endowments. Furthermore, both the probability of participation in fruit and vegetable cultivation as well as land allocation to horticulture decreases with the size of landholdings in India. Small or medium holders do not appear to allocate a greater share of land to fruits or vegetables. However, the share allocated to vegetables is significantly higher if the family size is bigger, while the reverse is true in the case of fruits.